Local grape cultivars in Egypt: exploring their potential health benefits - Dahab, Abeer; Mahmoud, Rania; Abd El-Salam, Hemat; Mahmoud, Gehan; Ibrahim, Eman (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The biological activities of phytochemical compounds in grapes have recently attracted increasing attention due to their potential health benefits for humans. In this study, seven local grape cultivars of Egypt (Gharibi, Fayoumi, Bez El-Naka, Romy Ahmer, Edkawy, Matrouh Eswid and Baltim Eswid) were investigated to determine their phytochemical composition, antioxidant and antimicrobial activities. Tannins, total phenols, total flavonoids and resveratrol content of grape pulp and seed extract were measured. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and the ferric reducing antioxidant power (FRAP) assays were used to determine the level of antioxidant activity. Polyphenolic compounds were identified using Liquid Chromatography-Tandem Mass Spectrometry Technique (LC-MS/MS). The findings revealed that, the Edkawy and Baltim Eswid cultivars presented the highest content of tannins in the seeds (0.68 and 0.65 %, respectively), and total flavonoids in the pulp and seeds (0.06 and 0.08 %, respectively). Baltim Eswid showed the best total phenols content (0.11 %) in the pulp. Overall antioxidant capacity of grape seed extracts was extremely superior to that of the pulp, where Baltim Eswid was the best in this concern. The maximum values of resveratrol for pulp and seed (46.24 and 307.12 mg.100g-1, respectively), were observed in Baltim Eswid. The main compounds found in the seed extract were the catechins, ranging from 26.51 % in Fayoumi to 35.8 % in Bez El-Naka. The study demonstrated that grape seed extract has antimicrobial properties with potential application as an antimicrobial agent in the industrial area and as an alternative treatment in the medical sector.